IJTIHAD JARINGAN ISLAM LIBERAL: Sebuah Upaya Merekonstruksi Ushul Fiqih - Mustofa, Imam (Islamic University of Indonesia, 2006)
Islamic legal theory denotes an original methodology of Islamic studies. This methodology is used by Moslem scholars especially Moslem jurists to understand Islamic teaching. The characteristics of this methodology is departing from texts either Quran or prophet tradition. Besides, human reason is also used in this methodology to understand and apply the Islamic doctrine. Based on this paradigm, it is clear that the forms of Islamic legal reform should consider revelation texts, reason and reality. Hence, this methodology differs from that of liberal Moslem scholars who try to offer Islamic legal reform is only using reason and rational understanding toward Quran and hadis because of social change and the complexity of problem.